Clinical Impact of Delayed Initiation of Adjuvant Chemotherapy Among Patients With Stage II/III Gastric Cancer: Can We Do Better? - Chen, Qi-Yue; Liu, Zhi-Yu; Zhong, Qing; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Huang, Ze-Ning; Lin, Ju-Li; et al. (Frontiers in Oncology, 2020)
Background: To investigate the prognostic effects and risk factors of the omission and delay of postoperative chemotherapy of stage II/III gastric cancer (GC). Methods: The clinicopathological data of 1,520 patients undergoing radical gastrectomy for stage II/III GC were collected and retrospectively analyzed. We defined the chemotherapy delayed until more than 60 days after radical gastrectomy and the complete omission of chemotherapy as unacceptable chemotherapy initiation (UAC), whereas the chemotherapy conducted within 60 days of radical gastrectomy was defined as acceptable chemotherapy initiation (AC). The survival between the two groups was compared, and the trends and risk factors of UAC were analyzed. Results: There were 539 (35.5%) patients with UAC. The overall survival (OS) and disease-free survival of the UAC group patients were significantly inferior to those in the AC group (p < 0.001). Cox multivariate analysis demonstrated that UAC is an independent predictor of OS (p < 0.05). The OS and disease-free survival of the patients in the UAC group were close to those of the patients without chemotherapy (p > 0.05). Logistic analysis showed that female, old age, a self-paid status, a very low social status, high American Society of Anesthesiologists scores, intra-abdominal surgery history, and serious postoperative complications were independent risk factors of UAC (all p < 0.05). The radar chart shows the risk factors of UAC changed with time. Conclusions: UAC after radical gastrectomy is an independent risk factor for the prognosis of stage II/III GC patients. However, no significant decline of UAC has been achieved recently and should call for the attention of both government and clinicians.